A case of methamphetamine use disorder presenting a condition of ultra-rapid cycler bipolar disorder. (February 2019) - Ikawa, Haruki; Kanata, Sho; Akahane, Akihisa; Tochigi, Mamoru; Hayashi, Naoki; Ikebuchi, Emi
Methamphetamine, a potent psychostimulant, may cause a condition of mood disorder among users. However, arguments concerning methamphetamine-induced mood disorder remain insufficient. This case study describes a male with methamphetamine-induced bipolar disorder not accompanied by psychotic symptoms, who twice in an 11-year treatment period, manifested an ultra-rapid cycler condition alternating between manic and depressive mood states with 3- to 7-day durations for each. The conditions ensued after a bout of high-dose methamphetamine use and shifted to a moderately depressive condition within 1 month after the use under a treatment regimen of aripiprazole and mood stabilizers. The cycler condition may be characteristic of a type of the bipolar disorder and a sign usable for characterization. Further efforts are needed to seek distinctive features and to improve diagnostic assessment of methamphetamine-induced mood disorders.